Heat transfer behaviors in a tube with combined conical-ring and twisted-tape insert - Promvonge, P.; Eiamsa-ard, S. (My University, 2007)
Heat transfer, friction factor and enhancement efficiency characteristics in a circular tube fitted with conical-ring turbulators and a twisted-tape swirl generator have been investigated experimentally. The heat transfer test section is heated electrically imposing axially and circumferentially constant wall heat flux boundary conditions. In the experiments, two enhancement heat transfer devices are applied. One is the conical-ring used as a turbulator and placed in the tested tube and the other is the twisted-tape swirl generator placed at the core of the conical-ring. Air as the tested fluid is passed both enhancement devices in a Reynolds number range of 6000 to 26,000. Two twisted-tapes of different twist ratios, Y = 3.75, and 7.5, are introduced in each run. The experimental results reveal that the tube fitted with the conical-ring and twisted-tape provides Nusselt number values of around 4 to 10% and enhancement efficiency of 4 to 8% higher than that with the conical-ring alone. A maximum heat transfer rate of 367% and enhancement efficiency of around 1.96 is found for using the conical-ring and the twisted-tape of Y = 3.75. For all the devices used, the enhancement efficiency tends to decrease with the rise of Reynolds number and to be nearly uniform for Reynolds number over 16,000. In addition, correlations for Nusselt number, friction factor and performance evaluation criteria to assess the real benefits in using the turbulator and swirl generator of the enhanced tube are determined. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Conical-ring turbulator; Friction factor; Heat exchanger; Heat transfer enhancement; Turbulent/reverse flow; Twisted-tape